2010
DOI: 10.1016/j.envint.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Brominated flame retardants in offices in Michigan, U.S.A.

Abstract: Brominated flame retardants (BFRs) are now ubiquitous contaminants with large reservoirs and high concentrations in buildings. Most of the information documenting BFR levels has been obtained in residences, and other environments that can lead to exposure have received relatively little attention, including offices that contain numerous BFR sources and where individuals spend considerable time. The aim of this study is to characterize BFR concentrations, potential emission sources, and migration pathways in of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
57
5
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 18 publications
12
57
5
5
Order By: Relevance
“…It is believed that pentaBDEs and octaBDEs are continually present on the surface of furniture, consumer electronics, carpets, textiles, and building materials in indoor workplaces in Taiwan. In an American study (Batterman et al, 2010), BDE-47, -71, and -99 were detected in most indoor dust, suggesting that currently on the market consumer products or household appliances were still significant sources of PBDEs despite the 2004 phaseout of pentaBDEs and octaBDEs in commercial products. Indoor PBDE concentrations may be influenced by several environmental factors including ventilation, room temperature, building materials, and numbers and types of consumer electronics (de Wit et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that pentaBDEs and octaBDEs are continually present on the surface of furniture, consumer electronics, carpets, textiles, and building materials in indoor workplaces in Taiwan. In an American study (Batterman et al, 2010), BDE-47, -71, and -99 were detected in most indoor dust, suggesting that currently on the market consumer products or household appliances were still significant sources of PBDEs despite the 2004 phaseout of pentaBDEs and octaBDEs in commercial products. Indoor PBDE concentrations may be influenced by several environmental factors including ventilation, room temperature, building materials, and numbers and types of consumer electronics (de Wit et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported high levels of PBDEs in dust from offices, retail stores, libraries, and other workplaces (Harrad et al, 2008;Batterman et al, 2010;Watkins et al, 2013;Xu et al, 2015b). Not much is known on accumulation of PBDEs in air-conditioner filters even through central air-conditioning systems and independent air conditioners have been widely used in many indoor environments such as offices, schools, laboratories, commercial buildings, and retail stores (Ni et al, 2011;Besis et al, 2014;Xu et al, 2015b;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Halogenated (usually brominated or chlorinated) flame retardants (HFRs) are chemicals that are extensively used in consumer products, including electronic equipment, textiles, furniture, and cars, to improve their resistance to fire (Batterman et al, 2010). A class of HFRs known as polybrominated diphenyl ethers (PBDEs), tetrabromobisphenol A (TBBPA), hexabromocyclododecane (HBCD), and Dechlorane Plus (DP) have become a topic of great concern because of their widespread occurrence in the environment and potential adverse effects on humans and wildlife (Cetin and Odabasi, 2007;Qiu et al, 2007;Harrad et al, 2009;Covaci et al, 2011;Ali et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, limited information on indoor air contamination of DecaBDEs can be found. The indoor air levels of DecaBDEs reported from other countries (medians < 42 pg/m 3 ) (Fromme et al, 2009;Johnson-Restrepo and Kannan, 2009;Batterman et al, 2010;Bjorklund et al, 2012) were much lower than the levels in the present study, except that higher concentrations (medians ¼ 130e3800 pg/ m 3 ) were found in Sweden (especially in offices and daycare centers) Thuresson et al, 2012). The substantially lower indoor air levels of PBDEs (except for DecaBDEs) in the present study were probably attributed to less rigorous fire prevention standard in China than in North America and Europe, which results in the small use of BFRs in indoor products and lower emission from the products.…”
Section: Concentrationsmentioning
confidence: 99%